Analysis Creative Thinking Pattern on X Sains 2 at SMAN 2 Jember to Solving Open Ended Problem of Space and Shape - Elsa Yuli Kurniawati; Dafik Dafik; Arif Fatahillah (CGANT JOURNAL OF MATHEMATICS AND APPLICATIONS, 2020)
Math learning to train people to think critically, creatively, logical, analytical and systematic. In reality, mathematics is often regarded as the science that emphasizes logical thinking with a unique solution and certainly, so that students do not have the flexibility to develop creative ideas. The condition causes low creativity of students in learning mathematics. Curriculum 2006 stated that creative thinking skills needed to master the science of the future, given that today's science and technology is developing very rapidly \cite{BSNP}. Thus, the ability to think creatively is important to develop. This study describes the rate and the process of creative thinking class X IPA 2 SMA Negeri 2 Jember, in solving open ended problems. Instruments used in this research is to test the ability to think creatively package A and package B, questionnaires and interview guidelines. Of the 36 students of class X IPA 2 SMA Negeri 2 Jember included TBK 0 (not creative) as much as two students (5.56%), TBK 1 (less creative) as many as twenty students (55.56%), TBK 2 (enough creative) thirteen students (36.1%), TBK 3 (creative) only one student (2.78%) and no students were able to achieve TBK 4 (very creative). Because there are only four levels of creative thinking then taken four students as research subjects who identified the creative thinking process. Students TBK 3 very fulfilling to aspects of fluency and flexibility aspects, but for the novelty aspect is still lacking. Students TBK 2 only meet the flexibility aspect alone. Students TBK 1 which fulfills the eloquence alone. Students who do not meet the TBK 0 fluency aspect, the aspect of flexibility and novelty aspect.